Secure Hybrid Scheme For Securing Mqtt Protocol Based On Enhanced Symmetric Algorithm - Hintaw, Ahmed Jameel (2023)
Internet of Things (IoT) enables device and machine communication using TCP/IP protocol. Message Queuing Telemetry Transport (MQTT) is the most preferred protocol and is expected to be the de facto messaging IoT standard. Therefore, MQTT must achieve efficient security. Nevertheless, the most significant drawback of the MQTT is its lack of protection mechanisms which verifies only simple security objects such as non-encrypted authentication and authorization policies, and even there is no encryption mechanism. Data could be altered by intruders while in transit. Researchers have proposed various security techniques to address these issues. Meanwhile, the existing schemes for protecting the MQTT network have added processing overhead to the devices but remain vulnerable for various attacks. Therefore, this research work presented an integrated scheme known as “Secure Hybrid Scheme”, to protect the MQTT protocol against any exploitations that might result in sophisticated cyberattacks. The proposed cryptosystem utilized two algorithms: a dynamic variant of the Advanced Encryption Standard (D-AES) and Key policy attribute base encryption (KP-ABE). A secure hybrid scheme introduces a new design architecture of the symmetric AES algorithm to encrypt the MQTT payload called “D-AES”. The key expansion unit has been strengthened in the D-AES.